‘It's a girl!’ Is gender disappointment a mental health or sociocultural issue? - Chrissy Jayarajah (BJPsych Bulletin)
Gender disappointment can be defined as subjective feelings of sadness when discovering that the sex/gender of a child is the opposite of what the parent had hoped or expected. Wanting a boy (or ‘son preference’) has long been noted in many cultures, particularly in South and East Asian communities, but it is now becoming more recognised in the UK, Europe and North America. This article aims to improve understanding of gender disappointment by exploring medical and social sciences research; it also discusses the clinical and risk implications of assessing and managing gender disappointment (or not doing so) when individuals present to perinatal and/or community mental health services.